A non-expensive bidimensional assessment can detect subtle alterations in gait performance in people in the early stages of Parkinson’s disease - d'Alencar, Matheus Silva; Santos, Gabriel Venas; Helene, André Frazão; Roque, Antonio Carlos; Miranda, José Garcia Vivas; Piemonte, Maria Elisa Pimentel (Frontiers in Neurology, 2023)
Background: Gait is one of the activities most affected by the symptoms of Parkinson's disease and may show a linear decline as the disease progresses. Early assessment of its performance through clinically relevant tests is a key factor in designing efficient therapeutic plans and procedures, which can be enhanced using simple and low-cost technological instruments. Objective: to investigate the effectiveness of a two-dimensional gait assessment to identify the decline in gait performance associated with Parkinson's disease progression. Methods: 117 people with Parkinson's disease, classified between early and intermediate stages, performed three clinical gait tests (Timed Up and Go, Dynamic Gait Index, and item 29 of the Unified Parkinson's Disease Rating Scale), in addition to a six-meter gait test recorded by a two-dimensional movement analysis software. Based on variables generated by the software, a gait performance index was created, allowing a comparison between its results with the results obtained by clinical tests. Results: There were differences between sociodemographic variables directly related to the evolution of Parkinson's disease. Compared to clinical tests, the index proposed to analyze gait showed greater sensitivity and was able to differentiate the first three stages of disease evolution (Hoehn & Yahr 1 and 2: p = .03; Hoehn & Yahr 1 and 3: p = .00001; Hoehn & Yahr 2 and 3: p = .02). Conclusion: Based on the index provided by a two-dimensional movement analysis software that uses kinematic gait variables, it was possible to differentiate the gait performance decline among the three first stages of Parkinson's disease evolution. This study offers a promising possibility of early identification of subtle changes in an essential function of people with Parkinson's disease.